Measuring and Analyzing Sovereign Risk with Contingent Claims - Gapen, Michael; Gray, Dale.; Lim, Cheng; Xiao, Yingbin (Washington, D.C. : International Monetary Fund, 2005)
This paper develops a comprehensive new framework to measure and analyze sovereign risk. Since traditional macroeconomic vulnerability indicators and accounting-based measures do not address risk in a comprehensive and forward-looking way, the contingent claims approach is used to construct a marked-to-market balance sheet for the sovereign, and derive a set of credit-risk indicators that serve as a barometer of sovereign risk. Applications to 12 emerging market economies show the risk indicators to be robust and highly correlated with market spreads. The framework can help policymakers design risk mitigation strategies and rank policy options using a calibrated structural model unique to each economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet